Profitability and Tax Avoidance: Exploring the Role of Financial Distress as a Driver of Tax Strategies - Muhammad Yogi Muslim (International Forum of Researchers and Lecturers, 2025)
This study investigates the effect of profitability, measured by Return on Assets (ROA), on tax avoidance, represented by the Effective Tax Rate (ETR), while considering financial distress (Z-Score) as a moderating variable. The research focuses on consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period, involving a sample of 35 firms. The study is motivated by the challenges faced by companies under financial pressure, where profitability and tax strategies often intersect. By employing multiple linear regression and Moderated Regression Analysis (MRA), this research provides empirical evidence on how financial distress influences the relationship between profitability and tax avoidance. The findings reveal that profitability has a significant negative effect on tax avoidance, indicating that more profitable companies tend to engage less in tax avoidance. However, when financial distress is present, this relationship intensifies—companies experiencing financial pressure are more likely to adopt aggressive tax avoidance strategies, even if they are profitable. This suggests that financial distress acts as a catalyst, amplifying the tendency to minimize tax obligations. The study contributes to the literature by offering insights into the moderating role of financial distress in corporate tax behavior, particularly in the Indonesian context. These findings have practical implications for policymakers and regulators in designing more effective tax compliance frameworks and understanding corporate financial risk during economic downturns.